Au nanoparticles supported on nanorod-like TiO2 as catalysts in the CO-PROX reaction under dark and light irradiation: Effect of acidic and alkaline synthesis conditions. (8th January 2019) - Rodríguez-Aguado, Elena; Infantes-Molina, Antonia; Talon, Aldo; Storaro, Loretta; León-Reina, Laura; Rodríguez-Castellón, Enrique; Moretti, Elisa
Abstract: Gold nanoparticles precipitated-deposited on titania nanostructures (1.0 wt% nominal loading) were studied in the preferential CO oxidation in excess of H2 at room temperature and atmospheric pressure, both in dark and under simulated solar light irradiation. Titania supports were synthesized by means of two hydrothermal methods markedly acid and basic, giving rise to rutile nanorods and anatase deformed nanorods structures, respectively. Characterization techniques such as N2 physisorption, XRD, XPS, DRUV-vis, HRTEM and XRF were performed in order to study the chemical, structural and optical properties of the catalysts. Well defined rutile nanorods structures were obtained from the acidic treatment allowing a regular distribution of gold nanoparticles and resulting quite active in the CO-PROX reaction. In particular the sample from the acidic synthetic approach calcined at 700 °C displayed the best results as it was highly selective to CO2 under both dark and simulated solar light irradiation. Graphical abstract: Image 1 Highlights: Preferential CO oxidation in H2 -rich stream under dark and simulated sunlight at R.T. TiO2 supports, synthesized by acidic or basic hydrothermal methods, play a different role in dispersing and growing Au NPs. Photo-response of Au NPs (<3.5 nm) on rutile and anatase nanorods structures. Catalysts with Au particle size ≤2 nm very active in the CO-PROX at ambient conditions. With Au NPs larger size, the catalyst behaves as a real photocatalyst, with a 100% of CO2 selectivity.